NLP for business excellence winning business games - Hall, L. Michael (Jaico Publishing House, 2010)
NLP for Business Excellence reveals not only the games that experts play to win, but the successful ways to play them. As you read this book you will learn to play games that work for you, and you will understand that successful game-playing involves changing your frame of mind ? because it is only when you change your own frame, and replicate the frame of a business expert, that you too will become a consistently, habitually successful business person. Presenting unique insights into the minds of successful business experts, this revelatory book applies powerful techniques from the sphere of Neuro-Linguistic Programming that will target your behavior and transform you into a brilliant player. It then coaches you in games for personal empowerment, teaching you how to win at specific games that address: positioning yourself; making work meaningful and satisfying; handling things; being your own best boss; adding value to the lives of others; resolving conflicts; inventing even better games.